Synthesis and Anti-HCV Activities of 18β-Glycyrrhetinic Acid Derivatives and Their In-Silico ADMET Analysis - Zhang, Kai-Xia; Wang, Peng-Ru; Chen, Fei; Qian, Xi-Jing; Jia, Lin; Liu, Xiao-Juan; Li, Lin; Jin, Yong-Sheng (Current Computer - Aided Drug Design, 2021)
Background: Licorice is widely used as a hepatoprotective herb for thousands of years in Traditional Chinese Medicine, and its main chemical constituent glycyrrhizin (GL) is used as a treatment for chronic hepatitis in Japan for over 20 years. 18β-Glycyrrhetinic acid (GA) is the main active metabolite of GL. Objective: Series of GA derivatives were designed and synthesized, and their anti-HCV activities were screened to investigate the structure-activity relationship (SAR). Besides, their in-silico ADMET properties were analyzed to search for a promising lead compound for further identification of anti-HCV terpenoid candidates. Methods: GA derivatives were synthesized via reactions of oxidation, oxime, rearrangement, esterification and acylation. In vitro anti-HCV activity of derivatives was tested on the HCV cell culture (HCVcc) system. In-silico ADMET properties analysis was performed via “pkCSM” and “SwissADME” platforms. Results: Eighteen GA derivatives were synthesized, and their structures were confirmed by MS and NMR spectrums. All compounds exhibited superior HCV inhibitory activity to that of GA. Compound 2 possessed the most potent anti-HCV activity with an IC50 value of 0.79 μM, which is nearly 58 times potent than SA (a previously reported potent anti-HCV terpenoids) and >200 times than GA. SAR revealed that the introduction of 3-oxo, short-chain (C1-C3) aliphatic alcohols or cyclic aliphatic amines is conducive to improving anti-HCV activity. In-silico ADMET prediction demonstrated most of the potent compounds possessed favorable ADMET properties. Conclusion: Structural modification of GA at 3-position and 30-position is an effective approach to searching for potent anti-HCV agents. Compound 2, with the most potent anti-HCV activity and favorable in-silico ADMET properties, is a promising lead compound for further identification of anti-HCV terpenoid candidates.
Keywords: terpenoids